Penyusunan Indeks Kelayakan Huni berdasarkan Data Citra Satelit dan Point Of Interest (POI) - Jannah, Rofa Raudhatul; Marsisno, Waris (Politeknik Statistika STIS, 2024)
Urban livability refers to a city that is fit to live in or the term livable city. The increasing number of urban zoned areas makes livability information important for urban planning and governance. However, livability assessments are often limited by data availability and update cycles, and data collection is expensive. Therefore, this research intends to explore urban liveability by utilizing big data in the form of satellite imagery and POIs, focusing only on information that can be extracted by these two sources. The method of compiling the livability index follows the OECD (2008) rules using factor analysis to determine the weight of indicators and constituent factors. There are 3 main constituent factors, namely the environmental sustainability factor, the public facilities factor and the industrial and commercial zone factor. Finally, the index mapping results show that there is a spatial pattern trend in the livability index in Bandung City.